Adoption Restraints in Mobile Banking with Reference to India - Deepa Damodaran; R. Regin; S. Suman Rajest (Research Parks Publishers, 2024)
The number of people using mobile banking has been steadily growing over the past few years. Most of the time, this is the case in countries that are still developing or underdeveloped. It is proposed to investigate the comparative significance and distinctive influence of communication channels on customers' theories and attitudes regarding the adoption of mobile banking in India. This is despite the fact that the technology that provides services to the satisfaction of the user has not yet been investigated.